2007
DOI: 10.1002/uog.3904
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial variability index in utero: a three‐dimensional ultrasound study

Abstract: K E Y W O R D S:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 12 publications
2
27
0
1
Order By: Relevance
“…1,2,22 In fetuses with DS, increased skeletal orbital height (in accord with the current result in Italian subjects but in contrast with that in North Sudanese ones) and interocular distance (in good accord with the current findings, especially in North Sudanese subjects) were found. 16 In contrast, in a three-dimensional ultrasonographic study, Roelfsema et al 17 found that a 29-week-old fetus with DS had significantly (92 SDs) reduced bony orbital dimensions (interocular and outer ocular distances) when compared with normal fetuses of the same gestational age. For both studies, no information about the ethnicity of their fetuses was reported, and only further investigations may help in better understanding of these contrasting data.…”
Section: 4y7mentioning
confidence: 92%
See 1 more Smart Citation
“…1,2,22 In fetuses with DS, increased skeletal orbital height (in accord with the current result in Italian subjects but in contrast with that in North Sudanese ones) and interocular distance (in good accord with the current findings, especially in North Sudanese subjects) were found. 16 In contrast, in a three-dimensional ultrasonographic study, Roelfsema et al 17 found that a 29-week-old fetus with DS had significantly (92 SDs) reduced bony orbital dimensions (interocular and outer ocular distances) when compared with normal fetuses of the same gestational age. For both studies, no information about the ethnicity of their fetuses was reported, and only further investigations may help in better understanding of these contrasting data.…”
Section: 4y7mentioning
confidence: 92%
“…Scanty data were provided by Farkas et al 10Y13 and Bagic and Verzak 9 whereas recent investigations analyzed orbital skeletal measurements in normal and DS fetuses. 16,17 Development of the structures of the upper facial third is strictly related to forebrain development, and alterations in orbital characteristics may derive from cerebral malformations in the embryonic and fetal period. 1,22 In the current study, the faces of 2 groups of subjects with DS (Italian white and North Sudanese) were imaged in 3 dimensions using computerized instruments, and the morphologic features of their orbital soft tissues were quantitatively analyzed using indirect, computerized anthropometry.…”
mentioning
confidence: 99%
“…Certains auteurs ont proposé d'établir un index de variabilité craniofaciale qui pourrait aider à l'évaluation de la face foetale [6]. Une étude critique de cet article montre que les index les plus élevés correspondent à des malformations sévères aisément identifiables en échographie 2D, alors que les dysmorphies plus subtiles (trisomie 21, syndrome d'Allagille) échappent au diagnostic.…”
Section: La Faceunclassified
“…Its modifications have been correlated with syndromic features, especially in fetuses with cleft lip/palate. 8,9 The role of 3D ultrasound is also unique in achieving a subjective evaluation of the fetal face:…”
Section: Three-dimensional Ultrasound: Technical Aspects and Clinicalmentioning
confidence: 99%